Forget technique, think coordination! An example of how recent theoretical knowledge can reshape coaching practices - Chollet, D. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Expert performance is characterised by the ongoing co-adaptation of an individual`s behaviours with dynamically changing, interacting constraints. Efficient coaching intervention requires a good understanding of what these constraints are because, even at sub-elite and elite levels, some adaptations are less efficient than others and can be qualified as 'technical mistakes`. The purpose of this study is therefore to propose a typology of some of the most frequent technical mistakes encountered in front crawl and suggest coaching interventions to address them. The typology is based on the three parts of a typical swim race (start, swimming, turn) and each issue is addressed as follows: first, a five-level analysis of the technical mistake is offered and, second, a seven-level remediation procedure is suggested. This presentation will be illustrated by technical problem no. 24, in which swimmers display over gliding due to inappropriate coordination in catch-up mode. Becoming an expert swimmer requires the knowledge of a coaching team. Over the years, the accumulated knowledge about spatial-temporal parameters and progress in understanding human physiology have led to significant improvements in performance. More recent research investigations have suggested that a deeper understanding of the role of motor coordination in coping with constraints is essential to further improve such key performance parameters as propelling efficiency and race management. From this perspective, our presentation tries to bridge the gap between theory and practice by proposing concrete 'down to the pool` proposals.